2019
DOI: 10.1088/1361-6463/ab523a
|View full text |Cite
|
Sign up to set email alerts
|

Microporous networks of NiMn2O4 as a potent cathode material for electric field emission

Abstract: The electric field-induced sterling electron emission of NiMn2O4 microporous networks synthesized via the sol-gel auto combustion route was investigated. Some primary characterization techniques such as x-ray diffraction, Fourier-transform infrared spectroscopy, and Raman spectroscopy were performed to confirm the pure crystallinity and metal oxide (Ni–O and Cr–O) stretching vibrations and also to provide a molecular fingerprint of the NiMn2O4 porous network. The distinct field emission (FE) properties of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…This channel-like morphology is advantageous for productive field emission properties. 39 Figure 1e shows the FESEM micrographs of as-sintered samples for the dielectric and magnetic study, and the grain growth is confirmed in the nm range 2a] additionally confirm the average particle sizes of NdNiO 3 below 100 nm with weak agglomeration. Nanoparticles influence distinctively its magnetic and electrical transport properties compared to its bulk counterparts.…”
Section: ■ Experimental Sectionmentioning
confidence: 63%
See 3 more Smart Citations
“…This channel-like morphology is advantageous for productive field emission properties. 39 Figure 1e shows the FESEM micrographs of as-sintered samples for the dielectric and magnetic study, and the grain growth is confirmed in the nm range 2a] additionally confirm the average particle sizes of NdNiO 3 below 100 nm with weak agglomeration. Nanoparticles influence distinctively its magnetic and electrical transport properties compared to its bulk counterparts.…”
Section: ■ Experimental Sectionmentioning
confidence: 63%
“…The tiny peaks at 481 and 489 cm –1 (pinpointed in Figure b with black arrows) are associated with Nd–O–Ni and Ni–O–Nd coupling vibrations, which further reinforced the strong bonding between atoms in the orthorhombic system. , The surface morphology of NdNiO 3 used for the field emission study is displayed in Figure c,d, and it exposed microporous network-like images with an enriched conducting channel. This channel-like morphology is advantageous for productive field emission properties Figure e shows the FESEM micrographs of as-sintered samples for the dielectric and magnetic study, and the grain growth is confirmed in the nm range between 60 and 105 nm with average particle sizes ∼95 nm.…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…This implies that the FD distribution should be considered for calculation, which is a statistical function that provides the probability to discover an electron in a given electronic state. The work function was calculated using the described methods implemented in the Quantum Espresso code following the equationΦ=EvacEnormalfwhere E vac and E f are the electrostatic potential energy in a vacuum and Fermi energy.…”
Section: Resultsmentioning
confidence: 99%